THE ROLE OF THE NATION FROM THE COLONIAL ERA TO THE REFORMATION ERA IN SUPPORTING INDONESIA'S GASTRODIPLOMACY - Mohamad, Amirunnaufal; S., Miavania (SIYAR Journal, 2024)
In recent decades, the trend of gastrodiplomacy has become increasingly significant, where countries use their culinary uniqueness as a major attraction in building bilateral relations and strengthening public diplomacy. However, the problems that arise are the difficulty in determining a unified food that represents Indonesian culture; Adjustment of Indonesia's culinary image to suit international tastes without losing authenticity and uniqueness; Global competition in the field of gastrodiplomacy is getting tougher. The purpose of this study is to provide a treasure of the origin of the many archipelago menus and provide strategies that need to be done by the government and non-government in Indonesia's gastrodiplomacy. The results of this study show that the menus in Indonesia are inseparable from the role of the Nusantara kingdom as the largest producer of spices in the world. In response to this, the government has made various efforts to support Indonesia's gastrodiplomacy, but there are still gaps that need to be filled to perfect the diplomacy strategy. Further research on the strategy and technical implementation of Indonesia's gastrodiplomacy is recommended.